Application of Problem-Based Learning Model Based on Humanistic Theory in Developing Students' Learning Motivation in Grade III MI Al-Azkiya Pengalihan - Harsiah (Jurnal Profesi Pendidikan, 2025)
Learning motivation plays a crucial role in determining students’ learning success at the elementary level, as this stage shapes attitudes, interests, and learning character for future development. However, learning in many Madrasah Ibtidaiyah is still dominated by teacher-centered approaches that limit students’ active participation. This study aims to describe the planning, implementation, and outcomes of applying a problem-based learning model grounded in humanistic theory to enhance the learning motivation of Grade III students at MI Al-Azkiya Pengalihan. The study employed a qualitative approach using a fixed case study design, involving 20 Grade III students as research subjects. Data were collected through observation, documentation, and assessment of learning activities and motivation indicators. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings indicate that learning planning was conducted effectively in accordance with the principles of problem-based learning and humanistic theory. The implementation of learning successfully encouraged active student participation. Students’ learning motivation increased, as reflected in high levels of curiosity (90%), activeness in asking questions (75%), enthusiasm for reading and learning (80%), courage to express opinions (85%), and initiative in discussion (70%). These results demonstrate that a humanistic theory-based problem-based learning model is effective in fostering students’ learning motivation.